REDUCING SALT ADDED TO CEREAL-BASED FOODS - A POSSIBLE CONTEXT SPECIFIC STRATEGY FOR ACHIEVING SALT REDUCTION IN INDIA. (April 2021) - Shivashankar, Roopa; Garg, Vandana; Santos, Joseph Alvin; Johnson, Claire; Rogers, Kris; Raj, Thout Sudhir; Gupta, Priti; Amarchand, Ritivk; Krishnan, Anand; Prabhakaran, Dorairaj; Mohan, Sailesh
Abstract : Objective: Reducing dietary salt consumption is one of the World Health Organization's best buys. In India, about 80% of dietary salt comes from added salt during cooking at home or at table. In this study, we assessed whether or not adding salt to cereal-based foods such as roti or rice, which comprise the main staple food, is associated with higher salt intake in India. Design and method: We used population-based representative data from India collected during 2013-14. We estimated daily salt intake among 651 North and 540 South Indian adult participants who provided complete 24-hour urine samples. Participants were asked how many days a week salt was added to dough or rice cooked at home. We stratified the responses '0 days' as 'NO added salt' and the responses '1–7' as 'added salt'. We did linear regression of sodium intake and added salt to dough and rice after adjusting for age, gender, and residence. Results: Salt was added to dough and rice at least once a week in 67% and 62% of North India and 62% and 12% in South India, respectively. Salt intake was significantly higher among participants who added salt to the dough (8.09 vs. 7.03 gm compared those who did not) in North India. No association was found with added salt to rice in North India and to dough or rice in South India and urinary sodium excretion. (Table 1) Figure. No caption available. Conclusions: Roti and cooked rice are the most frequently consumed staple cereal-based foods in North and South India, respectively. Tailored public health messages on not adding salt to staple cereal-based foods, particularly to rotis in North India may contribute to salt reduction in India.